Prevalence of Pulmonary Tuberculosis among Prison Inmates at Mbarara Central Prison, South Western Uganda - Owokuhaisa, Judith (Adv Res, 2014)
AIMS: This study was conducted to determine the prevalence of tuberculosis among prison inmates at Mbarara Central prison DESIGN: A cross sectional study was carried out at Mbarara Central Prison in Mbarara district, Kiswahili cell in Mbarara municipality among female and male prison in mates between June 2012 to August 2012. A questionnaire was administered to each prison inmate who consented in writing and two sputum specimens were collected and examined by Ziehl-Neelsen technique. RESULTS: At the time of the study, the prison had 900 inmates (both males and females). A total of 648 in mates were screened and 248 inmates enrolled in the study. Of the 248 inmates, 5 inmates were new cases of TB while 29 inmates were already on TB treatment. The median age of participants was 28 years (23.5-33 IQR) and 96.4% were males with majority (22.6%) coming from Mbarara as a home district. The participants had stayed in prison for a median duration of 2 years (1-3 IQR) and 23.7% had ever been in prison before. The median number of inmates per cell was 140 (138-149 IQR) and inmates (female and male) had a body mass index of 21.4 (19.9-22.6 IQR) and 20.2 (19.2-26.7 IQR) respectively. Of the inmates evaluated, 68.8% reported cough for 2 or more weeks. Other symptoms reported were weight loss (in 40.7%) and night sweats (in 35.8%). Of the 248 inmates evaluated, 95 inmates were tested for HIV and 4.1% were HIV serology positive. CONCLUSION: The prevalence of TB in Mbarara Central prison South Western Uganda is low but calls for continued surveillance through regular TB screening.